Nitrogen use efficiency and nitrogen response of wheat varieties commonly grown in the Great Plains, USA - Dorsey, Nathaniel D. (Kansas State University, 2014)
Increasing nitrogen use efficiency (NUE) and nitrogen response in winter wheat could help producers reduce input costs associated with nitrogen fertilizers and decrease the negative environmental impacts of N loss. The objectives of this research were to i) establish if there are genetic differences in NUE and other related parameters among wheat varieties commonly grown in the Great Plains, ii) determine if there are differences in N response among select varieties with a range of NUEs, and iii) determine if NUE influences N response. This information could be useful in future breeding efforts as researchers seek to develop more efficient varieties. This was approached by conducting two separate studies, a large NUE study with 25 winter wheat varieties, and a smaller N Rate study with 4 varieties that represented a range of NUEs based on the preliminary results of the NUE study. The NUE study was conducted over the course of several seasons and locations, with treatments of consisting of N Rate and variety. The experiment was laid out in a strip-plot design and replicated four times at each location. In the 2010-11 and 2011-12 seasons it was planted at the Kansas River Valley Experiment Field in Rossville, KS. In the 2012-13 season the experiment was planted at two locations, one at Silverlake and another at Ashland Bottoms, KS. The experiment was again planted at two locations in the fall of 2013, in Ashland Bottoms, KS, and Hutchinson, KS. The wheat varieties were grown with two N rates, 0 kg N ha⁻¹ and 90 kg N ha⁻¹. Nitrogen use efficiency was calculated as the grain yield per unit of available nitrogen (sum of soil N and fertilizer N) and ranged from 22-30 kg of grain per kg of N and was strongly influenced by variety with a p<0.001. Several other related parameters, such as grain yield, nitrogen utilization efficiency, harvest index, and fertilizer use efficiency were also significantly affected by variety with a p<0.05. These data suggest there are significant genetic differences in how varieties use and transport nitrogen within their tissues to produce grain. The N Rate experiment was planted in two locations during the 2012-13 season at Silverlake and Ashland Bottoms, KS, and planted again in the fall of 2013 at Ashland Bottoms and Hutchinson, KS. This experiment was laid out in a split-plot design with four varieties and four nitrogen rates. The varieties selected for this study were Duster, Everest, Jagger, and Larned and the four N rates were 0, 33.6, 89.7, and 145.7 kg N ha⁻¹. The results showed significant differences in yield response among the varieties at only one location, Ashland Bottoms (p=0041). Although N response at Silverlake was not significant, mean grain yields between varieties was significant (p<0.001). Two additional parameters, NUE and harvest index (HI), were also significantly different between varieties at Silverlake, KS with a p<0.05, while no additional parameters were significant at Ashland Bottoms. Those varieties that had higher response, Everest and Jagger, also tended to have higher NUEs compared to the other two varieties, Duster and Larned. However, because of the contrasting results between locations, additional research is needed to develop firm conclusions. These results provide significant evidence to support varietal differences in nitrogen use due to genetics, and provide the opportunity for breeders to begin developing varieties with higher NUE and improved N response. However, additional research will be required to determine the specific traits responsible for these varietal differences and to determine the suitability of high NUE crops for meeting the nutritional requirements of the future.
Keywords: Nitrogen; Efficiency wheat; Agronomy varieties; Response; Agronomy (0285)